Moist Wound Healing Using Virgin Coconut Oil (VCO) Ointment to Improve Skin and Tissue Integrity in Type 2 Diabetes Mellitus Patients - Fantri, Nurfantri; Muna, Nasir; Nurlinda, Nurlinda; Saranani, Muhaimin; Akhmad, Akhmad (Madago Nursing Journal, 2025)
Introduction: Type 2 Diabetes Mellitus (T2DM) is a major global health concern frequently complicated by diabetic foot ulcers, which require effective wound care to prevent infection and accelerate healing. Moist Wound Healing (MWH) and Virgin Coconut Oil (VCO) have been recognized as complementary therapies that may enhance skin and tissue integrity. This study aimed to assess the effectiveness of combining MWH and VCO ointment on wound healing and pain reduction in a patient with a diabetic ulcer. Methods: This case study involved a T2DM patient presenting with a grade IV diabetic ulcer on the right foot. The intervention consisted of MWH combined with VCO ointment, administered three times at three-day intervals. Wound healing was evaluated using the Bates-Jensen Wound Assessment Tool (BWAT) to measure skin and tissue integrity, while pain intensity was assessed using the Numerical Rating Scale (NRS). Results: After three intervention sessions, notable improvements were observed. The BWAT total score decreased from 60 to 29, reflecting substantial tissue regeneration. The presence of healthy granulation tissue increased from 90% to 96%, indicating enhanced wound bed recovery. Additionally, the patient’s pain score decreased from 5 (moderate) to 2 (mild) on the NRS scale. Conclusion: The application of Moist Wound Healing combined with VCO ointment demonstrated effectiveness in improving skin and tissue integrity, enhancing granulation tissue formation, and reducing pain in a T2DM patient with a diabetic ulcer. This intervention shows potential as part of comprehensive wound care management; however, further studies with larger samples and extended observation periods are needed to strengthen these findings.